Development of self‐regulation amongst dental students in problem‐based learning curricula: A qualitative study - Kamran Ali (8861576) (2023)
Aims To explore the value of problem-based learning in the development of self-regulation amongst undergraduate dental students. Materials and Methods A qualitative approach using focus groups was used to explore the perceptions and experiences of the participants regarding the role of problem-based learning (PBL) in promoting self-regulation in undergraduate dental education. The study was carried out at a newly established dental institution in Qatar. Purposive sampling technique was used to recruit the participants. Invitations to potential participants were sent by e-mail through appropriate professional channels. All focus groups were transcribed verbatim, and data were imported into NVivo 12 and analysed thematically. Results A total of five focus groups were conducted with 37 participants which included 27 females and seven males from two different cohorts. Participants expressed their views on a range of issues related to the self-regulation in problem-based learning and also provided recommendations to enhance the learning experiences of students. PBL was perceived to be an appropriate and effective strategy to support student autonomy in construction of knowledge and developing problem-solving and interpersonal skills. However, the workload of the students can impact adversely on their motivation and time management skills. Conclusions This study provides useful insights into the concept of self-regulation in problem-based learning environments as perceived by the stakeholders at a newly established dental institution. The findings of this study may offer clarity on how problem-based learning can be best utilised to promote self-regulation in undergraduate dental education. Other Information Published in: European Journal of Dental Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/eje.12820